Social participation of community-dwelling older adults in western China: A latent profile analysis - Luo, Di; Yu, Shiqi; Wang, Jun; Zhu, Ying; Yang, Lining; Bai, Ruonan; Rao, Qianyi; Zhang, Qiang; Wu, Di; Wang, Feng; Zhao, Qinghua; Xiao, Mingzhao (Frontiers in Public Health, 2022)
Objective: Social participation has become a policy framework to deal with population aging. However, little is known about the social participation of older adults in western China, and extensive, multi-center, regional research is lacking. The research investigated the profiles of social participation of older adults in western China and explore the characteristics and factors influencing this participation. Method: This cross-sectional study was conducted in 3 provinces (Chongqing, Sichuan, Inner Mongolia) in western China, and included 3456 participants aged 60 years or older in March 2021 and Dec 2021. Social participation was assessed using the Chinese version of the Impact on Participation and Autonomy Questionnaire (IPA). A latent profiles analysis (LPA) was performed to extract latent profiles of older adults in western China. Chi-square test and multinomial regression analyses were used to identify differences between these classes. Results: Three social classes were found: high participation group (Class one, n = 872,25.3%), medium participation group (Class two, n =1903, 55.0%) and low participation group (Class, three, n= 681,19.7%). Compared with the participants in the high participation group, good self-care ability was an independent protective factor in the low participation group (self-care: OR=0.018, CI=0.005-0.062; mild dependence: OR=0.039, CI=0.011-0.139). Older adults who were taken care of by non-spouse primary caregivers were more likely assigned into medium participation group (OR=2.097, CI=1.501-2.930) rather than low participation group. Furthermore, the oldest-old, education level at primary school, having mobility or speaking impairment, no using assistive devices, and having the chronic disease were highly associated with the medium and low participation group (P＜0.05). Conclusions: A typology with three patterns based on a wide spectrum of social participation aspects in older adults in western China was identified. Healthcare professionals should early pay special attention to the predictors identified different classes, and distinguish older adults in low participation groups and make targeted interventions based on their characteristics.